The Impact of Magic Lift-The-Flap Books on Knowledge and Attitudes of Children Regarding Obesity Prevention at SD IT Iqra 2, Bengkulu City - Sevira Eka Azzahra; Lissa Ervina; Wisuda Andeka Marleni (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
The issue of imbalanced nutrition among elementary school children became a health problem that could impact children in the future, such as obesity. The effects could include health and psychosocial problems in children. One of the factors that caused this condition was the lack of knowledge and attitudes among children. As a result, the Magic Lift-The-Flap Book is an example of the kind of interactive media that might be utilized to enhance children's understanding and beliefs. This study examines the effect of the Magic Lift-The-Flap Book on children’s knowledge and attitudes regarding obesity prevention at SD IT Iqra 2, Bengkulu City. A quantitative pre-experimental study with a single-group pre-test and post-test design was conducted. The sample consisted of 40 fifth-grade students aged 10–12 years who were randomly selected from a population of 129. Data were collected via questionnaires and analyzed using the Wilcoxon Signed Rank Test. The result of this study indicated that students’ knowledge scores rose from a mean of 69.25 prior to the intervention to 88.00 following the use of the Magic Lift-The-Flap Book. Similarly, the average attitude score improved from 24.50 prior to the intervention to 36.58 after the intervention. These findings demonstrated that the Magic Lift-The-Flap Book exerted a statistically significant influence on children’s knowledge and attitudes toward obesity prevention at SD IT Iqra 2, Bengkulu City, as indicated by a p-value of <0.001. Therefore, the Magic Lift-The-Flap Book was expected to function as an engaging educational medium to enhance elementary school children’s knowledge and attitudes regarding obesity prevention Keywords: Obesity, Magic Lift-The-Flap Book, Knowledge, Attitude